2022
DOI: 10.1021/acscatal.2c03144
|View full text |Cite
|
Sign up to set email alerts
|

Broken Promises? On the Continued Challenges Faced in Catalytic Hydrophosphination

Abstract: In this Perspective, we discuss what we perceive to be the continued challenges faced in catalytic hydrophosphination chemistry. Currently the literature is dominated by catalysts, many of which are highly effective, that generate the same phosphorus architectures, e.g., anti-Markovnikov products from the reaction of activated alkenes and alkynes with diarylphosphines. We highlight the state of the art in stereoselective hydrophosphination and the scope and limitations of chemoselective hydrophosphination with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 146 publications
(203 reference statements)
3
26
0
Order By: Relevance
“…Additional primary phosphines and sterically hindered alkenes were also demonstrated as viable substrates, in recognition of the limitations of scope in hydrophosphination catalysis. 7 Throughout this study multiple light sources are demonstrated to be effective for this system and illustrate that commercially available bulbs are effective rather than specialty photoreactors, increasing the utility of this catalyst in exploratory reactions.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…Additional primary phosphines and sterically hindered alkenes were also demonstrated as viable substrates, in recognition of the limitations of scope in hydrophosphination catalysis. 7 Throughout this study multiple light sources are demonstrated to be effective for this system and illustrate that commercially available bulbs are effective rather than specialty photoreactors, increasing the utility of this catalyst in exploratory reactions.…”
Section: Introductionmentioning
confidence: 89%
“…A more thorough understanding of mechanism would inform a transition to a prefabricated copper(I) catalysts that may promote additional reactivity to address specific challenges in hydrophosphination catalysis. 7,12 Herein, we report direct evidence of a catalytically active copper(I)-phosphido intermediate and that divergent mechanistic steps occur in the catalysis depending on the alkene substrate. Data in support of these mechanisms include a Hammett analysis, modified catalytic reactions with radical traps, a comparison of copper precursors, catalytic reactions of proxy intermediates, isotopic labeling experiments, a zwitterionic trapping experiment, and stoichiometric model reactions.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations